Hegel and global politics: communitarianism or cosmopolitanism? - Burns, Tony (SAGE, 2014)
This article discusses Hegel’s views on global politics by relating them to the ‘communitarianism versus cosmopolitanism’ debate. I distinguish between three different theoretical positions and three different readings of Hegel, which I associate with the notions of ‘communitarianism,’ ‘strong cosmopolitanism’ and ‘weak cosmopolitanism’ respectively. Contrary to a commonly held view that Hegel is not a cosmopolitan thinker at all, in any sense of the term, I argue that he is best thought of as a weak cosmopolitan thinker rather than a communitarian or a strong cosmopolitan advocate of the idea of a world-state. In passing, the article refers to the relationship which exists between Hegel’s ideas and those of three Twentieth Century theorists who might be associated with these theoretical positions and these different readings of Hegel, namely, Carl Schmitt, Alexandre Kojève and Jurgen Habermas. The article also refers to the methodological problems which are confronted by readers of Hegel’s writings who wish to apply his ideas to the problems of global politics today. Here I refer to a distinction which I have made elsewhere between different kinds of reading, namely the interpretation, appropriation and the reconstruction of texts, which is especially relevant for readers of the works of Hegel.